On the unusual properties dielectric constant of the electric field of the free atmosphere - Т.А. Білий (Геофизический журнал, 2021)
On the basis of experimental data vertical distribution electric field strength of the atmosphere, the applied problem of fitting constants in the model of the average self-consistent electric field is solved.The model is based on the nonlinear Poisson equation. Such an approach is not trivial because generally known in meteorology interpolation exponential function describing the empirical distribution of the electric field, space charge density and conductivity with a height not quite correctly reproduce a stable stratification of the electric field. Since aircraft measurements are carried out in a natural environment, the dielectric constant is lost, which leads to underestimated values of the electron-ion concentration.This is due to the fact that the potential in situ is screened and the Gauss theorem does not hold for it, and if it does, then for the radius of the Gaussian sphere it is less than the Debye screening radius. For a large Gaussian sphere, only the near-wall part of the electrometer is experimentally determined, and the shielded (inner) part does not contribute to the field flux through the surface by the dynamic screening of the electron. The magnitude of the screening of electrons in air is very large due to the dynamic polarizability of the medium and consists of two parts — the Debye and ion-plasma screening spheres. This, in turn, requires a redefinition of the dielectric constant for correct reproduction of field measurements. Thus, the verification of the dielectric constant was carried out on different experimental data, and its values lie within the same limits as the values obtained from the classical relations of Penn, Debye, and Landau.